QuickBooks online - Ringstrom, David H. (John Wiley & Sons, Inc., 2025)
QuickBooks Online For Dummies, 2025 Edition helps you understand one of the most widely-used cloud accounting platforms worldwide. Choose the best subscription for your business, create invoices and credit memos, record sales receipts, pay bills, set up inventory items, track business checkbook and credit cards, print checks, process payroll and prepare payroll tax returns, simplify tax preparation, build a budget, balance accounts, back up your data and access it on any device-the list goes on and this beginner-friendly book teaches you how to do it all. Chock full of useful tips and tricks, this golden guide makes small business accounting through QuickBooks Online a breeze-saving you time and money. Plus, this edition covers the latest features and shows you how QuickBooks uses AI to make accounting even easier for you and your needs.
Keywords: QuickBooks; Small business -- Accounting -- Computer programs; Small business -- Finance -- Computer programs; Petites et moyennes entreprises; Comptabilité; Logiciels; Petites et moyennes entreprises; Finances; Logiciels